Development of atraumatic heel-stick procedures by combined treatment with non-nutritive sucking, oral sucrose, and facilitated tucking: A randomised, controlled trial. Issue 8 (August 2015) - Yin, Ti; Yang, Luke; Lee, Tsorng-Yeh; Li, Chia-Chi; Hua, Yi-Ming; Liaw, Jen-Jiuan
Abstract Background Preterm infants manifest pain and stress by behavioural agitation and state change. Few studies have explored the effects of combining nonpharmacological interventions, i.e. non-nutritive sucking, oral sucrose, and facilitated tucking, on infants' behaviours across painful procedures. Objectives To explore the effects of combined use of three nonpharmacological interventions (non-nutritive sucking, oral sucrose, and facilitated tucking) on infants' pain- and stress-related behaviours during four assessment phases: baseline, intervention, heel stick, and recovery. Design Prospective, randomised controlled trial. Setting Level III neonatal intensive care unit in Taipei. Method A convenience sample of 110 infants (gestational age 27–37 weeks) needing heel sticks was randomly assigned to five combinations of nonpharmacological treatments: (1) routine care, (2) non-nutritive sucking + facilitated tucking, (3) oral sucrose + facilitated tucking, (4) non-nutritive sucking + oral sucrose, and (5) non-nutritive sucking + oral sucrose + facilitated tucking. Outcomes were infants' withdrawal or stress (grimace, limb and trunk extension or squirming) and approach or self-soothing (sucking, sucking search, or mouthing; hand holding or grasping; and hand to mouth, face) behaviours. Results The frequency of infants' withdrawal behaviours decreased significantly when they received combinations of nonpharmacological interventions before heel stick. Specifically, grimace frequency decreased by 32.2%, 30.6%, 19.7%, and 13.8% in infants receiving oral sucrose + non-nutritive sucking + facilitated tucking, non-nutritive sucking + oral sucrose, oral sucrose + facilitated tucking, and non-nutritive sucking + facilitated tucking, respectively, compared to those receiving routine care across assessment phases. Furthermore, infants' frequency of limb and trunk extension or squirming decreased by 24.0% when they received non-nutritive sucking + oral sucrose + facilitated tucking compared to those receiving routine care. Infants' frequency of approach behaviours did not change significantly across all phases when they received non-nutritive sucking + oral sucrose + facilitated tucking, non-nutritive sucking + oral sucrose, and oral sucrose + facilitated tucking compared to those receiving routine care. Conclusions The combined use of nonpharmacological interventions (non-nutritive sucking + oral sucrose + facilitated tucking) effectively reduced the frequencies of infants' withdrawal behaviours, i.e. grimace and limb and trunk extension or squirming. Our results provide evidence supporting clinicians' incorporation of the combined use of facilitated tucking, oral sucrose, and non-nutritive sucking into clinical practice during painful procedures. Heel-stick procedures can be atraumatic when conducted while infants are stable and quiet, appropriately positioned, and stabilised and by offering facilitated tucking, oral sucrose, and non-nutritive sucking before gently sticking the heel and squeezing blood.